2016
DOI: 10.3390/polym8080269
|View full text |Cite
|
Sign up to set email alerts
|

3D Culture of Chondrocytes in Gelatin Hydrogels with Different Stiffness

Abstract: Abstract:Gelatin hydrogels can mimic the microenvironments of natural tissues and encapsulate cells homogeneously, which makes them attractive for cartilage tissue engineering. Both the mechanical and biochemical properties of hydrogels can affect the phenotype of chondrocytes. However, the influence of each property on chondrocyte phenotype is unclear due to the difficulty in separating the roles of these properties. In this study, we aimed to study the influence of hydrogel stiffness on chondrocyte phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
147
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 183 publications
(172 citation statements)
references
References 61 publications
5
147
0
1
Order By: Relevance
“…It has been reported that cell spreading, proliferation, and osteogenic differentiation of mesenchymal stem cells are all enhanced when cells were cultured in gels with faster relaxation [36]. However, the rapid stress relaxation characters of hydrogels promoted the de-differentiation of chondrocytes as they down-regulated the gene expression of COL II and aggrecan [37]. …”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that cell spreading, proliferation, and osteogenic differentiation of mesenchymal stem cells are all enhanced when cells were cultured in gels with faster relaxation [36]. However, the rapid stress relaxation characters of hydrogels promoted the de-differentiation of chondrocytes as they down-regulated the gene expression of COL II and aggrecan [37]. …”
Section: Resultsmentioning
confidence: 99%
“…Ashby plots describe the possible stiffness ranges of both a) naturally derived and b) synthetic hydrogels. The diagram is helpful to provide design guidelines in material selection of polymer hydrogels for engineering 3D mechanical microenvironments of stem cells …”
Section: Mechanical Properties Of Hydrogels For 3d Stem Cell Culture mentioning
confidence: 99%
“…In recent years, among hydrogels used in biomedical applications, gelatin methacrylate (GelMA) hydrogel became an attractive candidate due to gelatin's favorable biocompatible characteristics, and because it can be photocrosslinked to form a stable gel at body temperature (37°C) . Due to its compatibility, GelMA has been already proposed in some BTE studies for producing scaffolds for bone and chondral regeneration purposes . In vitro and in vivo mineralization characteristics of GelMA scaffolds and its composites have already shown very promising results for bone regeneration.…”
Section: Introductionmentioning
confidence: 99%